In spite of myself a memoir - Plummer, Christopher 1929-2021 (Knopf, 2009)
In this rollicking self-portrait from one of today's great actors, Plummer tells of his privileged Canadian upbringing, rich in Victorian gentility, and how he tore himself away from the ski slopes to break into the big, bad world of theater.